STUDI IDENTIFIKASI PASANGAN COMMERCIALLY PURE TITANIUM DAN UHMWPE UNTUK APLIKASI MATERIAL IMPLAN LUTUT - Rusdi, Firman Maulana; Cahyani , Arini Dwi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Orthopedics is a science that studies the human body skeleton. This field of science helps patients who experience joint and skeletal problems. One of the problems faced is the need for body frame components to be replaced, for example the knees. This replacement requires a man-made component, namely an implant. Implants can be made from metal, polymer, and ceramic. The biomaterial implant identification process includes X-Ray Diffraction analysis, hardness and tensile testing. XRD testing of CP–Titanium and UHMWPE using the Rigaku XRD tool. CP–Titanium hardness testing uses Vickers micro hardness, while for UHMWPE uses Shore D. CP–Titanium tensile testing uses a universal test machine with JIS Z2201 standards. Another material, namely UHMWPE, is tested using the same equipment as the ASTM D638 standard. The XRD test results for CP - Titanium show peaks of 35.3˚, 38.6˚, 40.2˚, namely the hexagonal structure of the compound element α - Ti. Meanwhile, UHMWPE material shows peaks (110) at 21.66˚ and (200) at 24.16˚. The peak data is an orthorhombic crystal structure, which is characteristic of polyethylene. The CP – Titanium hardness test results show an average hardness of 360.47 VHN. The hardness value of UHMWPE shows an average hardness of 48.5 Shore D. CP - Titanium tensile testing shows a maximum stress value of 534.4 MPa and a maximum strain value of 0.022. The UHMWPE tensile test showed an average maximum stress value of 23.87 MPa and an average maximum strain value of 1.36. The data above shows that the materials tested are CP - Titanium and UHMWPE. Hardness data indicates that these CP – Titanium and polyethylene materials are too soft for applications requiring wear resistance.